Influence of the Self-leadership Ability and Positive Psychological Capital of Design Major College Students on Their Future Maturity - Shuang, Hu; Jeong, Dubae (Journal of Educational Research and Policies, 2025)
This study explores the impact of the self-leadership ability and positive psychological capital of design major college students on their future maturity. Self-leadership ability refers to an individual’s ability to guide their behavior through self-motivation, goal setting, and self-regulation, whereas positive psychological capital encompasses psychological traits such as self-efficacy, optimism, hope, and resilience. This study used a literature review and theoretical analysis methods, combined with relevant research at home and abroad, to verify the important role of self-leadership ability and positive psychological capital in college students’ career planning and development. The results indicate that greater self-leadership ability and positive psychological capital can significantly enhance the future maturity of design students and help them better cope with career challenges. This study provides a theoretical basis for career education for design major college students and proposes corresponding training strategies.